2 0 1 7 x 3 + 2 0 1 6 x 2 + 2 0 1 5 x + 2 0 1 6 = 0
Let α , β and γ be the roots of the equation above .
Find the value of :
4 α 4 β 3 γ 3 + α 3 β 4 γ 3 + α 3 β 3 γ 4 2 0 1 7 ( α 3 − β 3 − γ 3 ) + 2 0 1 6 ( α 2 − β 2 − γ 2 ) + 2 0 1 5 ( α − β − γ )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Typo: 2 0 1 7 β 3 + 2 0 1 6 β 2 + 2 0 1 5 β = − 2 0 1 6
⎩ ⎪ ⎨ ⎪ ⎧ 2 0 1 6 α 3 + 2 0 1 5 α 2 + 2 0 1 4 α = − 2 0 1 6 2 0 1 6 β 3 + 2 0 1 5 β 2 + 2 0 1 4 β = − 2 0 1 6 2 0 1 6 γ 3 + 2 0 1 5 γ 2 + 2 0 1 4 γ = − 2 0 1 6
α + β + γ = − 2 0 1 7 2 0 1 6
α β γ = ( − 1 ) 3 2 0 1 7 2 0 1 6 = − 2 0 1 7 2 0 1 6
4 α 4 β 3 γ 3 + α 3 β 4 γ 3 + α 3 β 3 γ 4 2 0 1 7 ( α 3 − β 3 − γ 3 ) + 2 0 1 6 ( α 2 − β 2 − γ 2 ) + 2 0 1 5 ( α − β − γ )
= 4 ( α β γ ) 3 ( α + β + γ ) − 2 0 1 6 + 2 0 1 6 + 2 0 1 6
= 4 ( 2 0 1 7 2 0 1 6 ) 4 2 0 1 6
= 2 0 1 7 2 0 1 6 2 0 1 6
= 2 0 1 7
Typo:
2 0 1 7 α 3 + 2 0 1 6 α 2 + 2 0 1 5 α = − 2 0 1 6 2 0 1 7 β 3 + 2 0 1 6 β 2 + 2 0 1 5 β = − 2 0 1 6 2 0 1 7 γ 3 + 2 0 1 6 γ 2 + 2 0 1 5 γ = − 2 0 1 6
It should be one, just because
Log in to reply
Why should it be one?
Log in to reply
Because that'd be funny @Hung Woei Neoh
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Vieta's Formula - Higher Degrees
Since α , β , γ are roots of the given equation, hence:
2 0 1 7 α 3 + 2 0 1 6 α 2 + 2 0 1 5 α = − 2 0 1 6 . . . ( 1 )
2 0 1 7 β 3 + 2 0 1 6 β 2 + 2 0 1 5 β = − 2 0 1 6 . . . ( 2 )
2 0 1 7 γ 3 + 2 0 1 6 γ 2 + 2 0 1 5 γ = − 2 0 1 6 . . . ( 3 )
LHS of ( 1 ) − ( 2 ) − ( 3 ) gives the numerator while denominator is simply fourth root of ( α β γ ) 3 ( α + β + γ ) , but Vieta's formula give:
α + β + γ = α β γ = 2 0 1 7 − 2 0 1 6 so that denominator is simply fourth root of ( α β γ ) 4 which is ∣ α β γ ∣ . Therefore answer is:
2 0 1 7 2 0 1 6 2 0 1 6 = 2 0 1 7